Secondary Education in Argentina during the 1990s - Gorostiaga, Jorge M.; Acedo, Clementina; Xifra, Susana E. (Education Policy Analysis Archives, 2003)
The reform of secondary education has been a fundamental part of national educational policy in Argentina since the beginning of the 1990s. Along with the decentralization of responsibilities to provinces and a new structure of primary and secondary education, changes have affected the areas of curriculum design, teaching methods, teacher training, school management, and information and evaluation systems. This study describes the main policies on secondary education implemented during the last decade, including their objectives and rationales. Focusing on how the reform can be seen to relate to issues of access, quality and equity, the study presents an analysis of its implementation, and discusses some of its effects. We argue that political, economic and technical factors as well as the strategies chosen by the national government resulted in a limited implementation, and we highlight the need for considering more focused reform strategies, alternative models of teacher training, and a more active involvement of teachers.